(untitled) (Książnica Śląska, 2025)
The article analyzes 17th century Polish poems about the matrimonial peripeties of Old Polish widows and widowers. The main characters in the works are a man and a woman, whose archetypes were people of significant magnate families of the 17th century. It was noted that the same life situation (the loss of spouses and the desire to enter into another marriage) is presented differently. Pasquinade with a male protagonist is milder. On the contrary in lampoon about women as main character, they are definitely humiliated and condemned, which is related to the moral norms prevailing in the patriarchal society of the Polish-Lithuanian Commonwealth.